IDENTIFICATION OF FLUID MIGRATION IN HYDROCARBON ZONES USING INTEGRATION OF MICROTREMOR HORIZONTAL-TO-VERTICAL SPECTRAL RATIO (MHVSR) AND LOW FREQUENCY PASSIVE SEISMIC (LFPS) METHODS - Jannah, Tsamrotul
Injectiong fluid into wells near the reservoir is a strategy used to address issues in tight reservoirs. One such implementation was conducted in the "TS" Oil Field. Therefore, a fluid injection study was carried out to monitor injection activity in the field and support the evaluation of connectivity between injection wells and production wells. This study was conducted in an integrated manner using the Microtremor Horizontal-to-Vertical Spectral Ratio (MHVSR) method to obtain Vs sections and Low-Frequency Passive Seismic (LFPS) by utilizing VHSR and PSD-IZ attributes. The results showed that stations located near the wells had relatively higher VHSR and PSD-IZ values, with both indicating the same anomaly, as they are situated above the oil field. The VHSR values also provided insight into the fluid movement direction. For instance, the injected fluid in Well F was found to be flowing south, whereas other wells did not show similar anomalies, which might be attributed to differences in injection rates. Additionally, to determine depth anomalies based on the MHVSR method, a zone with high Vs anomalies was identified, indicating a barrier located between low Vs values. The low Vs is associated with the reservoir, which consists of sandstone in the "TS" oil field.